The impact of STING signaling on myeloid cells highlights macrophages as the major player in controlling Brucella abortus - de Andrade, Kívia Q.; de Queiroz, Nina M. G. P.; Mambelli, Fábio; Marinho, Fábio V.; Amaral, Marcelo P.; Amarante-Mendes, Joao Gustavo P.; Barber, Glen; Oliveira, Sérgio C. (Frontiers in Immunology, 2026)
IntroductionBrucellosis, caused by Brucella abortus (Ba), is one of the most common zoonoses worldwide. Some components of the bacteria can be recognized by the innate immune system and understanding these mechanisms is necessary for directing future vaccines and therapies against brucellosis. Our group has demonstrated that STING molecule contributes to host protection against Ba in vivo. Considering that Ba has ability to subvert the immune response, the study of the mechanisms of host cell activation becomes fundamental for the development of measures to control bacterial replication. Currently, there is no data reporting which innate immune cell is important for STING-dependent control of Ba infection.MethodsTherefore, we used conditional knockout animals for STING in dendritic cells (CD11c-SKO) and in macrophages (LysM-SKO). WT, LysM-SKO and CD11c-SKO mice were infected with 1×106 CFU of Ba intraperitoneally. In parallel, BMDMs and BMDCs from WT, CD11c-SKO and LysM-SKO mice were infected with Ba (MOI 100) for 17 hrs. Next, we evaluated CFU and histology of the liver in vivo and LDH, cytokines and pyroptosis in vitro.Results and DiscussionInfected LysM-SKO mice, but not SKO-CD11c, showed an increase in CFU compared to infected WT animals. In vitro, the supernatant of infected BMDMs and BMDCs from LysM-SKO and CD11c-SKO animals showed decreased LDH and IL1-β and TNF-α when compared with WT cells. The absence of STING in infected BMDMs decreased the amount of cleaved caspase-1, -11 and GSDMD, evaluated by western blot analysis. The effect of lack of STING was more profound in macrophages than dendritic cells on innate signaling. In both BMDC and BMDM, the absence of STING did not affect NLRP3 expression. Together, these data indicate that STING signaling in macrophages and not in dendritic cells is important to control Brucella infection in vivo and impacts on inflammasome signaling pathway.